Management of Character Education in Discipline Development - Halomoan Marpaung; Sutaryat Trisnamansyah; Husen Saeful Insan; Waska Warta (International Journal of Nusantara Islam, 2017)
The development of social, cultural and economic forms of human growth today is based on character development as an inseparable part of every human individual. Management of Character Education Management in Discipline Development is part of forming human resources towards sustainable life. Resume & Eulogy Theory as the basis of research. Qualitative method through a process of observation, documentation and interviews developed with a triangulation system. Research questions 1) How is Character Education Planning in Discipline Development; 2) How to Organize Character Education in Discipline Development; 3) How is the Implementation of Character Education in Discipline Development; 4)) How to Supervise Character Education in Discipline Development. The results showed that the Character Education Planning in Discipline Development is defined as an attitude in which the development of knowledge, attitudes and skills is balanced. In the process of organizing all the components of the work unit structure in governance put forward the goal of building the character of the discipline itself. Implementation, the form of development of the educational implementation process leads to the formation of discipline in line with the basic goals of education. Supervision is arranged in line with the planning that human resources aim at achieving its goals.